Utilization of Tik Tok Social Media as Learning Media in the Teaching and Learning Process during Covid-19 - Ratna Susanti; Hamka Hamka (Yayasan Adra Karima Hubbi, 2024)
Background. The Covid-19 outbreak that occurred at the end of 2019 spread rapidly in Indonesia. To reduce the transmission, the Government set a rule not to hold activities that trigger crowds and all activities are carried out at home. The impact of this policy is very much felt, one of which is in the field of education. The learning system has changed significantly from face-to-face learning in classrooms to distance learning through online media. Efforts that can be made so that learning is still carried out during covid-19 are utilizing social media as a learning medium, one of which is through the Tik Tok application. Purpose. The purpose of this study was to determine the utilization of Tik Tok social media as a learning medium in the teaching and learning process during covid-19. Method. The research method used is quantitative method, data obtained from interviews and distributing questionnaires via google form. Results The results showed that Tik Tok social media was able to motivate students in learning because of Tik Tok's interesting and fun features. In addition, educators can also be creative through videos in presenting learning materials so that learning indicators can be conveyed. Conclusion. The conclusion of this study shows that the use of Tik Tok social media in the learning process during Covid-19 is very effective.